2020
DOI: 10.1002/slct.202003054
|View full text |Cite
|
Sign up to set email alerts
|

Triazole‐Modified Molybdenum Oxide with High Proton Conductivity

Abstract: Nowadays, the research of proton conductive materials has been extended from traditional sulfonated polymers to novel crystalline solid materials. It is important but still challenging to develop high-performance proton-conducting materials suitable for proton exchange membrane fuel cells (PEMFCs). Considering the features of molybdenum oxide and triazole in the construction of proton-conducting material, two triazole-modified molybdenum oxides, [MoO 3 (trz) 0.5 ] 1 and [H(atrz) 4 [(atrz) 2 (γ-Mo 8 O 26)] ⋅ 2H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Zhou Li and coauthors 83 (2) were synthesized, and the proton conductivity was studied at different RHs. Compound 1 showed proton conductivities of 7.19 × 10 −7 S/cm at 60% RH and 1.68 mS/cm at 95% RH.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou Li and coauthors 83 (2) were synthesized, and the proton conductivity was studied at different RHs. Compound 1 showed proton conductivities of 7.19 × 10 −7 S/cm at 60% RH and 1.68 mS/cm at 95% RH.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study conducted by Liu et al, the proton-conducting capabilities of triazolemodified α-MoO 3 were investigated. 50 Another prior investigation conducted by Whittingham examined the proton conduction properties of h-MoO 3 after acid treatment, which involved a preliminary analysis and focused on comparing the movement of hydrogen within various oxides. 51 In the current study, compound 1 demonstrates a significant level of proton conduction, reaching a value of 4.9 × 10 −3 S cm −1 at a temperature of 55 °C under a relative humidity of 98%.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The exploration of the proton-conducting characteristics of molybdenum oxide polymorphs is rather limited. In a previous study conducted by Liu et al, the proton-conducting capabilities of triazole-modified α-MoO 3 were investigated . Another prior investigation conducted by Whittingham examined the proton conduction properties of h -MoO 3 after acid treatment, which involved a preliminary analysis and focused on comparing the movement of hydrogen within various oxides .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the mechanism of proton conduction have shown that transport resources and the mechanism of Grotthuss prevail in the transfer of protons. 48 Polymeric N-heterocycles are often used to form mixed acid-base ion exchange membranes. The most common approach to the formation of acid-base membranes comprises the doping of polymers bearing the basic groups with mineral acids, sulfuric, or phosphoric.…”
Section: Introductionmentioning
confidence: 99%
“…Triazole‐modified molybdenum oxide showed proton conductivity that depending on temperature and humidity, can reach 1.94·10 −2 S/cm (85°C, 95% relative humidity). Studies of the mechanism of proton conduction have shown that transport resources and the mechanism of Grotthuss prevail in the transfer of protons 48 …”
Section: Introductionmentioning
confidence: 99%